Marginal resection for patients with atypical lipomatous tumours of the extremities and trunk wall: a systematic review and meta-analysis. (2nd December 2021) - Kido, Akira; Kitagawa, Yasuyuki; Tsukushi, Satoshi; Iwata, Shintaro; Ishida, Yukako; Tsukamoto, Shinji; Kawai, Akira
Abstract: Background: This systematic review assessed and compared the efficacy of marginal resection to wide resection in patients with atypical lipomatous tumours (ALT) by evaluating the local recurrence rates, overall survival and adverse event rates. Methods: We evaluated studies published between 1 January 1990 and 31 January 2019. The risks of bias in the selected studies were analyzed using the Cochrane Collaboration Risk of Bias Tool. The quality of the evidence was evaluated using the Grading of Recommendations, Assessment, Development and Evaluation approach. Results: Three case–control studies and three case series studies were identified. A meta-analysis was performed of six studies to evaluate the local recurrence rate after resection. Comparison of marginal and wide resections showed that the local recurrence rate was not significantly higher in the marginal resection group (14.2 and 1.4%, odds ratio: 2.88, 95% confidence interval 0.99–8.33, P = 0.05). We observed no difference in overall survival. In one study, the rates of adverse events were 14.7% in the marginal resection group and 45.4% in the wide treatment group (odds ratio, 0.32; 95% confidence interval 0.11–80.91, P < 0.05). Conclusions: In our analyses, five of six studies reported no recurrence for wide resection, compared to three to seven recurrences in the marginal resection group. One study reported only one case of recurrence for wide resection. Because ALT has a relatively good prognosis, the use of marginal resection is acceptable to preserve musculoskeletal function. Abstract : We performed a systematic review to assess the efficacy of marginal resection for atypical lipomatous tumour/well-differentiated liposarcoma compared to wide resection. Our data suggested that marginal resection is acceptable.